Risk reporting: A review of the literature and implications for future research✩. Issue 1 (31st January 2018) - Elshandidy, Tamer; Shrives, Philip J.; Bamber, Matt; Abraham, Santhosh
Abstract : This paper provides a wide-ranging and up-to-date (1997–2016) review of the archival empirical risk-reporting literature. The reviewed papers are classified into two principal themes: the incentives for and/or informativeness of risk reporting. Our review demonstrates areas of significant divergence in the literature specifically: mandatory versus voluntary risk reporting, manual versus automated content analysis, within-country versus cross-country variations in risk reporting, and risk reporting in financial versus non-financial firms. Our paper identifies a number of issues which require further research. In particular we draw attention to two: first, a lack of clarity and consistency around the conceptualization of risk; and second, the potential costs and benefits of standard-setters' involvement.